The joy of understanding mathematics: How emotions emerge from students’ beliefs and social experiences of learning mathematics at university - Göller, Robin; Lahdenperä, Juulia; Gildehaus, Lara (Finland, 2026)
This paper aims to better understand the interconnectedness of students’ emotions, beliefs, and experiences situated in the specific context of university mathematics education. Therefore, interviews with six students from three different universities in Finland and Germany were analysed using a thematic reflexive analysis. The findings identified the distinction between calculating and proving, the role of the subjective experiences of understanding, and the importance of social interactions for emotion regulation as key themes. It will be detailed and discussed how emotions emerge from different beliefs and experiences regarding these themes.